2010
DOI: 10.1056/nejmoa1000552
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Early versus Late Initiation of Dialysis

Abstract: In this study, planned early initiation of dialysis in patients with stage V chronic kidney disease was not associated with an improvement in survival or clinical outcomes. (Funded by the National Health and Medical Research Council of Australia and others; Australian New Zealand Clinical Trials Registry number, 12609000266268.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
608
2
17

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 774 publications
(659 citation statements)
references
References 27 publications
19
608
2
17
Order By: Relevance
“…A study in 2009 suggested that among nursing home residents with advanced kidney disease, initiation of dialysis was associated with a substantial and sustained decline in functional status 4. A provocative clinical trial from Australia and New Zealand in 2010 suggested that planned early initiation of dialysis in patients with Stage 5 CKD was not associated with improved survival or other clinical outcomes 3. These data have been supported by an increasing number of observational studies across different dialysis populations 33.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in 2009 suggested that among nursing home residents with advanced kidney disease, initiation of dialysis was associated with a substantial and sustained decline in functional status 4. A provocative clinical trial from Australia and New Zealand in 2010 suggested that planned early initiation of dialysis in patients with Stage 5 CKD was not associated with improved survival or other clinical outcomes 3. These data have been supported by an increasing number of observational studies across different dialysis populations 33.…”
Section: Discussionmentioning
confidence: 99%
“…Management strategies have largely focused on slowing down progression to end‐stage renal disease (ESRD), at which time, patients are invariably expected to transition to renal replacement therapy, mostly in the form of maintenance dialysis treatment 2. Nevertheless, recent data suggest that attempts to delay or even prevent transition to dialysis therapy may not be inappropriate,3 including a 2009 study that showed that the initiation of dialysis was associated with a substantial and sustained decline in functional status of the elderly nursing home patients 4. Many patients with kidney disease prefer to opt to exhaust all conservative management options for CKD, including nutritional strategies, prior to considering dialysis therapy 5…”
Section: Introductionmentioning
confidence: 99%
“…However, 76% of patients randomly assigned to start at low eGFRs actually started at higher levels because of uremic signs and symptoms, resulting in a relatively small difference in eGFRs between the groups. 6 The study failed to show a survival difference between those randomly assigned to start dialysis therapy with higher and lower eGFRs, possibly because of this relatively small difference, but suggested that clinical status is important in the decision making of nephrologists. [6][7][8] Nevertheless, little is known about exactly which criteria nephrologists use in their decision for when to start dialysis therapy.…”
mentioning
confidence: 98%
“…While urgent initiation of HD may seem like the only option, timing is usually flexible. Early HD has failed to improve survival, 26,27 and many patients may die before reaching the point of inevitable HD. 28 Peritoneal dialysis is a viable option for many 29 that is underutilized in the US.…”
Section: Respect For Autonomy: Patients Are Often Provided Neither Inmentioning
confidence: 99%
“…6 A recent push toward earlier initiation of HD has failed to improve survival. 26,27 Best supportive care for elderly ESRD patients has achieved a 1-year overall survival of 65 %, which rivals survival on HD. Of those patients, 71 % died at home 60 -a central goal for many patients.…”
Section: Nonmaleficence: the Harms Of Hemodialysis Often Outweigh Itsmentioning
confidence: 99%